THE DEVELOPMENT OF LEARNING ACTIVITY PACKAGE USING GENERATIVE AI TO ENHANCE THE ENGLISH WRITING SKILLS OF GRADE 9 STUDENTS THROUGH IMAGE CREATION - Pawapaiboon, Wiwansa; Amnuaiphanwilai, Thaweesin (Journal of Education and Innovation, 2025)
This research aims to develop a learning activity package using Generative AI to create images to enhance the English sentence writing skills of Grade 9 students. The study was conducted at the Naresuan University Secondary Demonstration School of during the 2024 academic year, with a population of 269 Grade 9 students and a sample size of 38 students. This research is a development study in which the researcher designed a learning activity utilizing Generative AI to create images and had the learning activity package evaluated by 5 experts. The activity was then tested to compare the students' ability to write English sentences before and after participating in the learning activity package, along with evaluating the sample group’s satisfaction with the activity. The research findings indicated that the learning activity package was deemed highly appropriate ( = 4.71, SD = 0.55). Additionally, the trial showed a significant improvement in the sample group’s ability to write English sentences at the .05 level. Furthermore, the sample group expressed a high level of satisfaction with the learning activity package ( = 4.21, SD = 0.67).